Investigation of Heat Treatment and Friction Stir Processing Effects on Mechanical Properties and Micro Structural Evolution of Sc-Inoculated Al-Zn-Mg Alloys - NAIK, Dr. J. MURALI (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
This study investigates the effects of various artificial ageing parameters on Vickers hardness characteristics and the surface modification of scandium inoculated Al-Zn-Mg alloys through friction stir processing. The aluminium alloys were subjected to a solution treatment at 465°C for one hour, followed by quenching in water and artificial ageing at temperatures of 120°C, 140°C, and 180°C for varying durations up to twenty hours. In addition, friction stir processing was used to address casting porosity and refine cast microstructures. These microstructural changes resulted in a significant improvement in both the strength and ductility of the aluminium alloys (7xxx series). Generally, a high tool rotation rate proved beneficial in breaking down coarse second-phase particles, healing casting porosity, homogenizing the material, and consequently increasing strength. Thus, friction stir processing was adopted for microstructure modification in cast aluminium alloys to refine grain structure and enhance mechanical properties.